Compósitos e nanocompósitos de polietileno-celulose : efeito do tamanho e da composição da fibra e do processamento nas propriedades óticas e mecânicas dos filmes - Maia, Thiago Henrique Silveira (2017)
In this study an aqueous dispersion of a polyethylene copolymer with a content of 6 wt% of acrylic acid was used as an alternative medium for incorporation of cellulosic fibers (FC), nanofibrils (NFC) and lignocellulosic nanofibrils with 3 wt% of lignin (LCNF) from Eucalyptus grandis to compare the effect of size and composition on the properties of films obtained by casting and pressing. The amount of the fibers varied from 0 to 30%wt. The appearance, optical, thermal and mechanical properties as well as the film morphology were evaluated for comparison of fiber size and composition. The films are transparent up to 10%wt of FC and NFC, indicating good dispersion of the fibers, being brownish in the presence of NFLC. The addition of FC and NFC promoted improvements up to 900% in the Young modulus of the films. NFLC containing films showed superior Young modulus and tensile strength around 1700% and 35% higher than PE samples. Scanning electron microscopy (SEM) morphology of the films showed a good dispersion, but a poor distribution of the fibers through the matrix, with PE-rich and fiber-rich regions for the cast-processed composites and nanocomposites. In this way, the properties of NFC films were also evaluated after a extrusion step using two different screw rotations. SEM morphology of the extruded films revealed the occurrence of re-agglomeration and a consequent decrease on the aspect ratio of NFC into the PE matrix, with significant reduction of the Young's modulus and transparency. In addition, the polyolefin aqueous dispersions processed by casting seem to be a promising and relatively fast route for obtaining polyolefin/cellulose nanocomposites films, but the interconnected web like morphology of NFC must be preserved for obtaining better mechanical properties.